Oxidative Stress and Cardiovascular Complications in Type 2 Diabetes: From Pathophysiology to Lifestyle Modifications - Alfredo Caturano; Maria Rocco; Giuseppina Tagliaferri; Alessia Piacevole; Davide Nilo; Giovanni Di Lorenzo; Ilaria Iadicicco; Mariarosaria Donnarumma; Raffaele Galiero; Carlo Acierno; Celestino Sardu; Vincenzo Russo; et al. (Antioxidants, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that significantly increases the risk of cardiovascular disease, which is the leading cause of morbidity and mortality among diabetic patients. A central pathophysiological mechanism linking T2DM to cardiovascular complications is oxidative stress, defined as an imbalance between reactive oxygen species (ROS) production and the body’s antioxidant defenses. Hyperglycemia in T2DM promotes oxidative stress through various pathways, including the formation of advanced glycation end products, the activation of protein kinase C, mitochondrial dysfunction, and the polyol pathway. These processes enhance ROS generation, leading to endothelial dysfunction, vascular inflammation, and the exacerbation of cardiovascular damage. Additionally, oxidative stress disrupts nitric oxide signaling, impairing vasodilation and promoting vasoconstriction, which contributes to vascular complications. This review explores the molecular mechanisms by which oxidative stress contributes to the pathogenesis of cardiovascular disease in T2DM. It also examines the potential of lifestyle modifications, such as dietary changes and physical activity, in reducing oxidative stress and mitigating cardiovascular risks in this high-risk population. Understanding these mechanisms is critical for developing targeted therapeutic strategies to improve cardiovascular outcomes in diabetic patients.